Changes in char structure due to inorganic matters during anthracite pyrolysis - Gong, X.; Zhang, Shu (Elsevier, 2017)
© 2017 Elsevier B.V. To understand effects of inherent mineral matters on the evolution of char structure, the microcrystalline structures of chars from the pyrolysis of raw, HCl-washed (CW) and HCl & HF-washed anthracites (CFW) were investigated by X-ray diffraction (XRD) respectively. Stacking height (Lc), interlayer spacing (d 002 ) and crystallite width (La) were used as parameters for char structure estimation. The results showed that with increasing contents of inherent mineral matters, Lc of char decreased, whereas d 002 and La increased. To study effects of a single inorganic matter, CFW was impregnated with Al 2 O 3 , SiO 2 , and CaO respectively. It was found that all of them (oxides) have resulted in the decrease in Lc and increase in La and d 002 . Differing from Al 2 O 3 , SiO 2 , and CaO, the introduction of Fe 2 O 3 has caused the reduction for both La and Lc values simultaneously, especially when the Fe 2 O 3 contents in the coal were high.